Proceedings of the Conference on Continuous Advances in QCD 2004 : (World Scientific, 2004)
This book contains articles on the latest research in QCD from some of the leading experts in the field. These are based on talks presented at the Continuous Advances in QCD 2004 workshop held at the William I Fine Theoretical Physics Institute.